2018
DOI: 10.1103/physreva.98.013606
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization, condensate growth, and defect formation in an out-of-equilibrium Bose gas

Abstract: We experimentally and numerically investigate thermalization processes of a trapped 87 Rb Bose gas, initially prepared in a non-equilibrium state through partial Bragg diffraction of a Bose-Einstein condensate (BEC). The system evolves in a Gaussian potential, where we observe the destruction of the BEC due to collisions, and subsequent growth of a new condensed fraction in an oscillating reference frame. Furthermore, we occasionally observe the presence of defects, which we identify as gray solitons. We simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In Brown et al [11], we showed that an entire Bose condensate formed in a non-zero momentum state, as opposed to some components being in a metastable state as in the experiments with solitons and vortices. We used a Bragg pulse to excite 50% of a population of rubidium-87 atoms in the ground state of an approximately harmonic trap into the |2 hk momentum state.…”
Section: Introductionsupporting
confidence: 50%
“…In Brown et al [11], we showed that an entire Bose condensate formed in a non-zero momentum state, as opposed to some components being in a metastable state as in the experiments with solitons and vortices. We used a Bragg pulse to excite 50% of a population of rubidium-87 atoms in the ground state of an approximately harmonic trap into the |2 hk momentum state.…”
Section: Introductionsupporting
confidence: 50%
“…For many T = 0 non-equilibrium phenomena it is sufficient to treat this initial condition as a multimode coherent state that is sampled by seeding the initial mean-field condensate wavefunction with on average half an atom of vacuum noise per mode [48]. Zero temperature TW with this initial condition has successfully modelled BEC dynamics in regimes where nonclassical particle correlations become important [49][50][51][52][53][54][55][56][57][58]. For finite-temperature studies, the relevant c-field theory is the stochastic projected Gross-Pitaevskii equation (SPGPE), which describes interactions between degenerate modes of the quantum field with a static thermal reservoir [59].…”
Section: Classical Field Methodologymentioning
confidence: 99%
“…For many T = 0 non-equilibrium phenomena it is sufficient to treat this initial condition as a multimode coherent state that is sampled by seeding the initial mean-field condensate wavefunction with on average half an atom of vacuum noise per mode [47]. Zero temperature TW with this initial condition has successfully modelled BEC dynamics in regimes where nonclassical particle correlations become important [48][49][50][51][52][53][54][55][56][57]. For finite-temperature studies, the relevant c-field theory is the stochastic projected Gross-Pitaevskii equation (SPGPE), which describes interactions between degenerate modes of the quantum field with a static thermal reservoir [58].…”
Section: Classical Field Methodologymentioning
confidence: 99%